The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/jacs.5b08249
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of Materials Determined by Relayed Paramagnetic Relaxation Enhancement

Abstract: Particle and domain sizes strongly influence the properties of materials. Here we present an NMR approach based on paramagnetic relaxation enhancement (PRE) relayed by spin diffusion (SD), which allows us to determine lengths in the nm−μm range. We demonstrate the method on multicomponent organic polymer mixtures by selectively doping one component with a paramagnetic center in order to measure the domain size in a second component. Using this approach we determine domain sizes in ethyl cellulose/hydroxypropyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Therefore, with the analysis of the DNP enhancements and signal buildup times, it was possible to measure the size of the EC domains (Figure ). Simulation of the variation in the relayed DNP enhancements with polarization time indicated that the length of the EC domains was 0.2 μm, in good agreement with measurements of the EC domain size made using paramagnetic relaxation enhancement …”
Section: Applications Of Dnp‐enhanced Solid‐state Nmr Spectroscopy Tosupporting
confidence: 74%
See 2 more Smart Citations
“…Therefore, with the analysis of the DNP enhancements and signal buildup times, it was possible to measure the size of the EC domains (Figure ). Simulation of the variation in the relayed DNP enhancements with polarization time indicated that the length of the EC domains was 0.2 μm, in good agreement with measurements of the EC domain size made using paramagnetic relaxation enhancement …”
Section: Applications Of Dnp‐enhanced Solid‐state Nmr Spectroscopy Tosupporting
confidence: 74%
“…Models of 1 H spin diffusion have been widely applied in solid‐state NMR spectroscopy to understand diverse phenomena such as enhanced longitudinal relaxation and mixing and segregation of solid phases and to estimate the sizes of domains or particles . Numerical and analytical models of 1 H spin diffusion can be used to obtain a fundamental understanding of the factors that determine the magnitude of the DNP enhancements in relayed DNP experiments .…”
Section: Modeling 1h Spin Diffusion In Relayed Dnp Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…16−19 It has also been shown that the selection process can be replaced by selective doping of one of the domains of the diamagnetic system with paramagnetic species and using paramagnetic relaxation enhancement to estimate the domain sizes. 20 In these approaches, the initial out-of-equilibrium state is achieved by selective doping followed by either comparison with spin diffusion dynamics in an undoped sample or comparison to a state in which the doped region is hyperpolarized. The curves obtained through comparison of the two initial states for different recovery times in saturationrecovery experiments can then be interpreted using numerical solutions of the diffusion equations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The exponential scaling of spin dynamics simulations drastically limits the size of the spin systems that can be studied; as a result, researchers have developed innovative approximate solutions to the many-body dynamics involved in large groups of spins. Notable examples include the concept of spin temperature, 25 the modeling of spin diffusion using classical diffusion equations [26][27][28][29][30] or as a multistep rate process, [31][32][33][34] and the simulation of DNP in large spin systems using a kinetic Monte Carlo algorithm. [35][36][37] Recent efforts have been increasingly directed at reducing the size of the density matrix by removing unimportant, or unpopulated, states from the basis set such that fully ab initio spin dynamics simulations can be performed in spin systems containing hundreds of spin-1/2 nuclei.…”
Section: Introductionmentioning
confidence: 99%